Investigation on Aging Model of Solid Propellant Using the Degree of Crosslinking - Junqi Wang; Huiru Cui; Weili Ma (International Journal of Aerospace Engineering)
Solid propellant is the main part of solid rocket motor (SRM). To further investigate the service life of SRM, aging of solid propellant should be concerned. The aim of this study is to propose a new aging constitutive model of solid propellant using the degree of crosslinking. The aging development equation of viscoelastic Poisson’s ratio (VPR) and relaxation modulus are considered in establishing the model. A series accelerated aging experiments accompanied with some tensile tests are designed to verify the new model. Aging experiments show that degree of crosslinking (DCL) can be used to act as a link to facilitate the communication between chemical aging and aged mechanical parameters well.